Morphogenesis of the sexual phase of the epiphytic ferns Microgramma mortoniana and Pleopeltis macrocarpa (Polypodiaceae) Punta Lara Natural Reserve, Buenos Aires, Argentina - Gorrer, Daniel Alejandro (2018)
The Punta Lara Natural Reserve is located on the riverside of the La Plata River in the province of Buenos Aires, Argentina. It is the Southern most relict in the world of subtropical riparian forest. The epiphytic ferns studied in this work belong to the Polypodiaceae family: Microgramma mortoniana and Pleopeltis macrocarpa. Plant communities are subject to high levels of anthropization and introduction of exotic species. The goals of this work are to provide information on the morphogenesis of epiphytic gametophytes and to extend knowledge of their life cycles, contributing to their conservation. Sowing was carried out in Dyer medium. In both species the spores are monolete, ellipsoidal, yellowish and with verrucate sculpture. The equatorial diameter is 60-61 μm, the polar diameter is 39-42 μm. The germination is the Vittaria type; in M. mortoniana occurs at 20 days, while in P. macrocarpa occurs at six days. The filaments are uniseriate of 3-6 cells in length. The gametophyte development is Drynaria type. The cordated form is given after 40 days. In M. mortoniana, buds originated after 40 days. In P. macrocarpa, after 120 days, clathrate trichomes scale-like appear mainly on the margins of the gametophyte. The gametangia are typical of leptosporangiate ferns. The sporophyte of M. mortoniana emerged after 120 days and that of P. macrocarpa arose after 500 days, its blades are simple, spatulate and unicellular and multicellular branching hairs were observed. The germination pattern, gametophyte development, the presence of a lipid globule in the prothalic cell and the formation of unicellular capitated hairs are relevant characters that could be considered for systematic group. The delay in the formation of sporophytes through sexual reproduction, allows us to infer that the success of their establishment in situ would be given by the vegetative reproduction through creeping rhizomes and buds of gametophytes.